ANALISIS IMPLEMENTASI HIDDEN CURRICULUM DALAM PEMBENTUKAN KARAKTER SANTRI DI PESANTREN INDONESIA - Lasmanah, Lasmanah; Mukarom, Mukarom (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Character education in Indonesian pesantren takes place within a 24-hour communal ecosystem that integrates scholarship, spirituality, and social life. As a result, religious values, discipline, and morals are shaped not only through the formal curriculum but also through a hidden curriculum, which consists of norms, habits, role modeling, unwritten policies, as well as the physical and cultural environment of the pesantren. This study aims to explore the implementation of the hidden curriculum in shaping the character of santri (students) and to map research trends and the need for a more holistic conceptual model regarding its internalization mechanisms. The study employs a qualitative approach based on Systematic Literature Research (SLR) using the PRISMA procedure. Articles were collected in early February 2026 using PoP, resulting in 900 articles, which were then narrowed down to 72 articles for analysis. The study's findings show that publication trends have increased year by year, with qualitative methodologies dominating at 90%. The primary subjects are santri, accounting for 51.8%, and the most frequent interventions are routine activities at 17.7%. The research identifies seven aspects of character formation through the hidden curriculum in pesantren: routine habituation; role modeling and classical literacy; environmental ecosystem; social character and leadership; intellectual and skills development; physical well-being and healthy living behaviors; and the influence of rules, sanctions, and the language environment. These seven aspects are interconnected and mutually influence each other in the sustainable formation of character.